Analisis Keruangan Lahan Sawah Terhadap Luas Panen Padi Sawah Di Kecamatan Tomohon Barat - Edwin Lewan Kereh; Diane D. Pioh; Ronny Nangoi; Yani Kamagi Yani Kamagi (Universitas Sam Ratulangi, 2019)
ABSTRACTPaddy fields in Tomohon Barat District are local rice food suppliers, also one of the placesfor the community to make a living. The purpose of this study was to determine the area of paddyfields from 2014-2018 by using the ArcGIS and Google Earth applications and find out whetherthe area of paddy fields affected the area of paddy rice harvesting in Tomohon Barat District.This research was conducted in May to June 2020, located in West Tomohon District. Themethod used is the digitization method on screen. Secondary data was taken via the internet inBPS City Tomohon in Figures 2015-2019 and BPS District Tomohon Barat in Figures 2015-2017 as well as from the Agricultural Education and Forestry Extension Office of Tomohon BaratDistrict. The research was not conducted by field survey because it was in a Covid-19 pandemicsituation. The results showed that, the area of paddy fields in Tomohon Barat District from 2014-2018 had an area of 285-278 hectares or around 8% of the total area. The decrease in the area ofpaddy fields tends not to affect the harvested area of paddy in West Tomohon District. HarvestedArea in 2016-2018 tends to increase. This trend is influenced, among others, by the availabilityof water and the availability of labor.Keywords: Spatial Analysis, Paddy Field